Microdialysis-Assessed Exercised Muscle Reveals Localized and Differential IGFBP Responses to Unilateral Stretch Shortening Cycle Exercise - Nindl, Bradley C.; Ahtiainen, Juha; Gagnon, Sheila S.; Taipale, Ritva S.; Pierce, Joseph R.; Martin, Brian J.; Beckner, Meaghan E.; Lehti, M.; Häkkinen, Keijo; Kyröläinen, Heikki (Frontiers in Endocrinology, 2020)
Microdialysis allows for previews into metabolism and provides physiological insight that blood measurements cannot. PURPOSE: To examine IGF-I system regulation in interstitial fluid during unilateral stretch shortening cycle exercise. METHODS: 10 men (26±7 yr) performed unilateral jumping [stretch shortening cycle (SSC) exercise at 50% of optimal jump height] until fatigue on a sledge. Sampling occurred using a venous catheter, and 100 kDa microdialysis probes inserted into the thigh muscle of each exercise/control leg. Serum was drawn before (Pre; -3 h) and after SSC [Post I (+0 h), II (+3 h), or III (+20 h)]; dialysate was sampled for 2 h before (Pre), during/immediately after (Ex), and 3 h into recovery (Rec). IGF-I parameters were measured with immunoassays. Interstitial free IGF-I was estimated from dialysate IGF-I and relative recovery correction. Data were analyzed with repeated measures ANOVA. RESULTS: Serum total IGF-I increased +3 h (Post II: 182.8±37.6 vs. Pre: 168.3±35.0 ng/mL, p<0.01), but returned to baseline by +20 h (Post III vs. Pre, p=0.31). No changes in serum free IGF-I were noted. Serum BP-1 and -3 increased over baseline, but not until + 20 h after SSC (Post III vs. Pre: 7.6±4.9 vs. 3.7±2.3 and 1048.6±269.2 vs. 891.4±171.2 ng/mL, respectively). A decreased serum BP-6 +3 h after SSC (p<0.01), followed by a return to baseline at +20 h (p=0.64 vs. Pre) was observed. There were no changes in dialysate or ISF IGF-I in either leg (p>0.05). Dialysate BP-1 remained increased in both legs through 3 h into recovery (Rec vs. Pre, p<0.01). Dialysate BP-3 also demonstrated an increase over Pre SSC concentrations, but in exercise leg only (Ex and Rec vs. Pre, p<0.04). We observed a prolonged decrease in dialysate BP-5 (Ex and Rec vs. Pre, p<0.03); an increase in BP-4 IP in the exercise leg only. There were no changes in dialysate for BP-2 or -6. CONCLUSIONS: Unilateral exercise drives differential regulation of the IGF-I system at both local and systemic levels. More specifically, this study demonstrated that localized exercise increases IGFBP-3,